2021
DOI: 10.1002/adsc.202001498
|View full text |Cite
|
Sign up to set email alerts
|

Advances in C(sp2)−H/C(sp2)−H Oxidative Coupling of (Hetero)arenes Using 3d Transition Metal Catalysts

Abstract: C−H/C−H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl‐aryl, aryl‐heteroaryl, and heteroaryl‐heteroaryl couplings via double C(sp2)−H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth‐abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 209 publications
0
15
0
Order By: Relevance
“…Since these pioneering reports, it found manifold applications in organic synthesis. For example, the role of FeCl 3 in oxidative C—C coupling reactions has already been reviewed, [ 70 ] and its fundamental role in the synthesis of hexabenzocoronenes or related polyarenes been discussed. [ 71 ]…”
Section: Mechanosynthesis Of Hexabenzocorones Related Carbon Material...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since these pioneering reports, it found manifold applications in organic synthesis. For example, the role of FeCl 3 in oxidative C—C coupling reactions has already been reviewed, [ 70 ] and its fundamental role in the synthesis of hexabenzocoronenes or related polyarenes been discussed. [ 71 ]…”
Section: Mechanosynthesis Of Hexabenzocorones Related Carbon Material...mentioning
confidence: 99%
“…[ 72 ] As a result, a solvent‐free protocol for the synthesis of the benchmark hexabenzocoronene (HBC) with FeCl 3 as oxidant was developed ( Scheme 6 ). [ 70 , 71 ] Under optimized conditions, the authors were able to synthesize HBC in over 90% yield within a short milling time of 30 min. It was proven that chlorinated side‐products were suppressed by the correct choice of milling material as well as a reduced reaction time.…”
Section: Mechanosynthesis Of Hexabenzocorones Related Carbon Material...mentioning
confidence: 99%
“…9 In recent years, the CDC reaction has become one of the most active research areas in modern organic synthesis and has shown many successful synthetic applications. 10 While some reviews and books have covered transition-metal-catalysed CDC reactions, 11,12 this review herein mainly focuses on the advancement of Rh-catalysed CDC reactions for the construction of the C(sp 2 )–C(sp 2 ) bond with representative examples from 2016 to mid-2021 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…As a subset of C–H functionalization processes, cross-dehydrogenative coupling (CDC) reactions are attractive because they do not require prefunctionalized starting materials, relying instead on oxidative activation followed by a net loss of H 2 /H 2 O to facilitate new bond formation. 8–10 However, research on forging the cross coupled aryl C–N bonds, especially on the scope of the substituted benzene ring in cross C–N bond couplings, remained restricted, although some practical methods have been developed. 11–15 Among the recent advances in CDC aminations to phenols bearing C2-amino derivatives, Miura and co-workers reported a metal-chelation assisted approach enabling absolute C2-site selective aryl C–H functionalization to realize C2-site aminated products, where it was necessary to remove directing groups to give 2-aminophenols.…”
Section: Introductionmentioning
confidence: 99%